Autoecología de Elaeagía uxpanapensis D. Lorence (Rubiaceae), en la reserva biológica Alberto Manuel Brenes, San Ramón, Costa Rica - Brenes Cambronero, Liz (1999)
UCR::Investigación::Sistema de Estudios de Posgrado::Ciencias Básicas::Maestría Académica en Biología